2008
DOI: 10.4103/0256-4947.51687
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in type 2 diabetic patients

Abstract: BACKGROUND AND OBJECTIVESHealth-related quality of life (HRQOL) is an important health outcome, representing one of the most important goals of all health interventions. The objectives of this study were to determine HRQOL and the factors affecting it in type 2 diabetic patients.PATIENTS AND METHODSThis cross-sectional study was conducted in five primary health care (PHC) centers in the Al-Khobar area. From a random sample of 225 type 2 diabetic patients, 216 patients were included in the study along with 216 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
45
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 18 publications
(30 reference statements)
15
45
0
2
Order By: Relevance
“…Previous studies have not been able to demonstrate the combined impact of T2DM and impaired HRF on mortality because their samples included only people with diabetes (11,12). Research has shown that people with T2DM are more likely to experience impaired HRF compared with populations without diabetes (5,7,10). It is also well established that hyperglycemia promotes CVD risk through various mechanisms, including inflammation and endothelial dysfunction (19), which consequently increase atherosclerosis and plaque rupture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have not been able to demonstrate the combined impact of T2DM and impaired HRF on mortality because their samples included only people with diabetes (11,12). Research has shown that people with T2DM are more likely to experience impaired HRF compared with populations without diabetes (5,7,10). It is also well established that hyperglycemia promotes CVD risk through various mechanisms, including inflammation and endothelial dysfunction (19), which consequently increase atherosclerosis and plaque rupture.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is increasing evidence to suggest that poor HRF may predict the development of disease, e.g., in type 2 diabetes (T2DM) (8) and CVD (9). Because of the burden of the daily management of T2DM and the development of complications, HRF is particularly important for people with T2DM, with levels of health status shown to be compromised in these populations (5,7,10). Findings from previous studies show that in samples of patients with T2DM, persons reporting low levels of HRF have higher risk of mortality compared with those reporting high functioning (11,12).…”
mentioning
confidence: 99%
“…This association between diabetes and complications means that people with diabetes not only have shorter life expectancy than people without diabetes [8,9], but also experience poorer health-related quality of life (HRQoL) than the general population [10,11,12]. Moreover, patients with diabetes-related complications have lower HRQoL than diabetes patients without complications [13,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Recent interest in quality of life (QOL) as an outcome measure in medicine has inspired studies in chronic medical13 and general population subjects45 in Arab and neighboring countries. To further this interest, it is important to use assessment instruments that are psychometrically sound and have cross-cultural validity, so as to make findings comparable across countries.…”
mentioning
confidence: 99%